2017
DOI: 10.1002/hed.24789
|View full text |Cite
|
Sign up to set email alerts
|

Delayed lower cranial neuropathy after oropharyngeal intensity‐modulated radiotherapy: A cohort analysis and literature review

Abstract: Background To examine swallowing-related lower cranial nerve palsy (LCNP) in oropharyngeal cancer (OPC) survivors after intensity modulated radiotherapy (IMRT). Methods Patients treated with definitive IMRT (66–72 Gy) were pooled from trial databases. Prospective analyses on parent trials included videofluoroscopy, clinical LCNP examination, and questionnaires pre- and 6-, 12-, and 24-months post-IMRT. Time-to-event and incidence of LCNP was estimated with competing risk methods. Literature review (1977–2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 32 publications
(96 reference statements)
4
60
0
Order By: Relevance
“…Thereby, late LCNP was consistently associated with substantial functional morbidity among OPC survivors. These results are not surprising given the degree of swallowing dysfunction previously reported among long‐term OPC survivors in earlier case reports, which suggested that treatment‐related LCNP may play a major role in late RAD and precipitate delayed but extreme oropharyngeal impairment as recorded by MBS studies . These observations also align to numerous reports of significant swallowing dysfunction caused by lower CN deficits among populations (in the absence of head and neck RT) due to traumatic injury, vascular causes, and infection, documented primarily in case reports …”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Thereby, late LCNP was consistently associated with substantial functional morbidity among OPC survivors. These results are not surprising given the degree of swallowing dysfunction previously reported among long‐term OPC survivors in earlier case reports, which suggested that treatment‐related LCNP may play a major role in late RAD and precipitate delayed but extreme oropharyngeal impairment as recorded by MBS studies . These observations also align to numerous reports of significant swallowing dysfunction caused by lower CN deficits among populations (in the absence of head and neck RT) due to traumatic injury, vascular causes, and infection, documented primarily in case reports …”
Section: Discussionsupporting
confidence: 82%
“…Overall, late LCNP with accompanying dysphagia is a clinical condition of great concern as it does not typically respond well to treatment. With progressive long‐term functional decline with aspiration and recurring aspiration‐pneumonia, long‐standing feeding tube dependence and elective laryngectomy may be required . Therefore, risk reduction and management of late effects like LCNP, late‐RAD, and associated functional toxicities need to be prioritized in contemporary OPC treatment and management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations